Imagining the unknown - Responsible creativity for a better tomorrow - Lutnæs, Eva (FormAkademisk, 2015)
This paper explores the scientific discourse on creativity in the field of design education, drawing upon 165 papers presented at the DRS//CUMULUS Oslo 2013 conference. The review shows creativity to be a key concept in the scientific discourse and identifies five storylines that conceptualise creativity as a generic human capacity for which the field of design education eagerly claims responsibility. In the scientific discourse, the fostering of creativity is a leading motive when articulating reasons for design to gain terrain in general education. A multifaceted repertoire of strategies to solve design problems can drive new ideas or artefacts that contribute to both environmental protection and degradation, human aid or human-made disasters. I discuss how to frame the relevant educational content of creativity as part of a general education that empowers citizens to promote sustainability and meet global challenges ahead.